Palace of Schonbrunn, near Vienna - Wallis, William, b. 1796 (engraver):::Creator::::::::::::; Batty, Robert, 1789-1848 (artist):::Contributor:::::::::::: (Rodwell & Martin; London; United Kingdom)
Engraving of the front of the Schönbrunn palace with soldiers and other people walking about